Autologous full-thickness skin in the repair of complex ventral hernias: an innovative step into the future of complex hernia repair? - Holmdahl, Viktor; Strigård, Karin; Gunnarsson, Ulf (Frontiers in Surgery, 2023)
The repair of complex ventral hernias, such as giant incisional or parastomal hernia, is associated with a high risk for complications and recurrence. Some serious complications are related to implantation of synthetic mesh as reinforcement material. Autologous full-thickness skin graft (FTSG) as reinforcement material in the repair of these complex hernias may offer a safe alternative. This is a review of the history of FTSG use in hernia surgery and the experiences of our research group regarding its application over the last decade. The results of FTSG used in the repair of giant ventral hernias are promising, and this method may already be recommended in selected cases. We have also conducted a translational chain of preclinical studies, based on a murine model, to gain a greater understanding of the behaviour of FTSG implanted in various positions in the abdominal wall. The use of intraperitoneal FTSG as reinforcement material in parastomal hernia repair is currently being evaluated in a randomised, controlled, multicentre study.